Use of oral health care services in Peru: trends of socio-economic inequalities before and after the implementation of Universal Health Assurance - Akram Hernández-Vásquez; Guido Bendezu-Quispe; Diego Azañedo; Marilina Santero (BMC, 2019)
Abstract Background Oral health inequalities are profound worldwide. Despite major improvements in oral health, inequalities exist for many racial and ethnic groups, by socioeconomic status, gender, age, and geographic location. Therefore, the purpose of this study was to investigate trends of socio-economic inequalities in access to oral health services in Peru before and after the implementation of Universal Health Assurance (AUS). Methods Analytical cross-sectional study based on the National Household Survey on Living Conditions and Poverty (ENAHO) 2004, 2008, 2010 and 2017. Two periods were defined before and after the AUS Law (2009). Use of oral health services was the dependent variable, for the general population and according to ages, the area of residence, and natural region. Measurements of inequality in the use of health services were made based on the concentration curves (CC), dominance test and concentration index (CI). Results We included a number of 85,436 (2004), 88,673 (2008), 87,074 (2010) and 124,142 (2017) participants. The proportion of people who used oral health services was 8.4% (2014), 10.1% (2008), 10.6% (2010) and 10.4% (2017). Use of oral health services showed an increase in different age groups, urban and rural areas, and natural regions of residence during the study period. The CC were distributed below the line of equality, indicating an inequality of use of oral health services, in favor of the richest groups and dominance of the CC in 2017 over the previous years. Changes in the CI were statistically significant for < 5 years and in the rural area, and for the period 2010-2017 they were also significant in the general population, children aged 5-17 years, urban area, and Andean and Jungle regions, which indicates a reduction in the concentration of use of these services in these groups. Conclusions The use of oral health services in Peru increased and inequality decreased in the period 2004-2017, coinciding with the implementation of the AUS. However, the use of these services continue having a distribution in favor of the richest populations. It requires the introduction of new strategies and oral health programs in the Peruvian population, with the aim of closing the gap currently mediated by the economic possibilities.